Complex N-glycans or core 1-derived O-glycans are not required for the expression of stage-specific antigens SSEA-1, SSEA-3, SSEA-4, or Le(Y) in the preimplantation mouse embryo. - Williams, S; Stanley, P (2009)
The glycan epitopes termed stage-specific embryonic antigens (SSEA) occur on glycoproteins and glycolipids in mammals. However, it is not known whether these epitopes are attached to N- or O-glycans on glycoproteins and/or on glycolipids in the developing mouse embryo. In this paper the expression of the antigens SSEA-1, SSEA-3, SSEA-4 and Le(Y) was examined on ovulated eggs, early embryos and blastocysts lacking either complex and hybrid N-glycans or core-1 derived O-glycans. In all cases, antigen expression determined by fluorescence microscopy of bound monoclonal antibodies to embryos at the stage of development of maximal expression was similar in mutant and control embryos. Thus, none of these developmental antigens are expressed solely on either complex N- or core 1-derived O-glycans attached to glycoproteins in the preimplantation mouse embryo. Furthermore, neither of these classes of glycan is essential for the expression of SSEA-1, SSEA-3, SSEA-4 or Le(Y) on mouse embryos.